Oral cancer awareness and knowledge among residents in the Oporto city, Portugal. Issue 3 (15th May 2015) - Monteiro, Luís Silva; Warnakulasuriya, Saman; Cadilhe, Suzana; Sousa, Duarte; Trancoso, Pedro Ferreira; Antunes, Luís; Salazar, Filomena; Pacheco, José Júlio
Abstract: Objective: To assess the awareness and knowledge on oral cancer in a general population of Oporto city, in Portugal. Methods: Face‐to‐face interviews were performed with 1116 individuals, resident in the city of Oporto. Participants' socio‐demographic information, lifestyle habits and awareness, knowledge and beliefs on oral cancer were ascertained. Results: Breast cancer was the most mentioned being as heard of (69.8%), while oral cancer was one of the least heard of (23.7%). Tobacco was identified as a risk factor by 54.8% of individuals and this knowledge was associated with their education level ( P  < 0.001), dentist visits ( P =  0.026), and tobacco consumption ( P  < 0.001). Fewer subjects (24.6%) referred to alcohol as a risk factor, and this knowledge was associated with their education level ( P  = 0.020) and dentist visits ( P =  0.002). More than half the subjects (58.8%) could not identify any sign or symptom of oral cancer. Conclusion: There is a general lack of awareness on oral cancer among this Oporto population. Higher education level and better oral health care were significant factors that identified individuals with a better awareness and knowledge of oral cancer, suggesting that educational measures could be useful for the prevention and early diagnosis of oral cancer in the Portuguese population.